Nasal lavage levels of granulocyte‐macrophage colony‐stimulating factor and chronic nasal hypereosinophilia. Issue 6 (26th March 2015) - De Corso, Eugenio; Baroni, Silvia; Lucidi, Daniela; Battista, Mariapina; Romanello, Matteo; Autilio, Chiara; Morelli, Renato; Di Nardo, Walter; Passali, Giulio Cesare; Sergi, Bruno; Bussu, Francesco; Fetoni, Anna Rita; et al.
<x xml:space="preserve">Abstract</x> Background The aim of the present study was to measure levels of granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) in nasal lavage of patients affected by chronic eosinophilic sinonasal inflammation to clarify the relationship with eosinophilic tissue infiltration and clinical features. Methods Between November 2012 and June 2013, we selected 70 patients with chronic eosinophilic inflammation (average age 41.8 years) who were classified into the following groups: persistent allergic rhinitis (group 1), noninfectious non‐allergic rhinitis with eosinophilia syndrome (group 2) and chronic rhinosinusitis with polyps (group 3). Finally, we enrolled 20 healthy subjects as controls (group 4). All patients underwent symptoms score questionnaire based on a visual analogue scale, nasal endoscopy and/or computed tomography (CT) scan, and allergy testing. Nasal cytology by scraping of the mucosa and GM‐CSF assays in nasal lavage were performed in all subjects. Results Detectable levels of GM‐CSF were found in 34 of 70 (48.57%) patients, with an average concentration of 2.67 ± 0.8 pg/mL, whereas in controls only 1 of 20 individuals showed detectable GM‐CSF levels. Eosinophil infiltration was significantly higher in patients with detectable GM‐CSF compared to those with undetectable levels (49.4% vs 39.2%, respectively; p < 0.05). Furthermore, significant weakly‐moderate correlation was found between GM‐CSF levels and percentage of eosinophil infiltration in tissue (p < 0.05). Correlation between symptom scores and GM‐CSF levels was significant only in group 2, which showed higher average concentrations of GM‐CSF compared to groups 1 and 3 (2.9 pg/mL vs 1.6 pg/mL and 1.8 pg/mL, respectively; p < 0.05). Conclusion Our data confirm that GM‐CSF is more frequently detectable in nasal lavages of patients affected by chronic sinonasal eosinophilic inflammation than in controls. Statistical analyses revealed a significant weakly‐moderate correlation between GM‐CSF levels in nasal lavage of all patients and percentage of eosinophil infiltration of nasal mucosa.